Penerapan Hipnosis Lima Jari Untuk Penurunan Kecemasan Pada Pasien Diabetes Mellitus di Dusun Ngrendeng Kabupaten Sragen - Fransiska Falda Bachrani; Tri Susilowati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Background:Data obtained from Central Java, on average 40% of DM patients from those aged 40-69 suffer from DM, people who suffer from DM on average have feelings of anxiety about their disease. Anxiety is a vague feeling of restlessness due to discomfort or fear accompanied by a response that causes the individual to be unspecific or unknown. One way to treat anxiety is five finger hypnosis therapy. Objective: To describe the results of applying five finger hypnosis to the health of diabetes mellitus patients. Method: This study method uses the HARS (Hamilton Anxiety Rating Scale) Method: According to the HARS scale, there are 14 symptoms that appear in individuals who experience anxiety. Each item observed is given 5 levels of score (Likert scale) between 0 (Zero Present) to 4 (severe). Results: After performing hypnosis on Mrs. E and Mrs. R, which initially had a score of 27, became 20 and a score of 25 became 18. Conclusion: The application of five finger hypnosis therapy can reduce anxiety in Diabetes Millitus patients.